When Does Trust Matter to Alliance Performance? - Krishnan, Rekha; Martin, Xavier; Noorderhaven, Niels G. (Academy of Management Journal, 2006)
We examine how uncertainty moderates the trust-performance relationship in alliances, building on the distinction between behavioral uncertainty, which relates to anticipating and understanding partners' actions, and externally caused environmental uncertainty. We argue that trust matters more to performance under behavioral uncertainty and less under environmental uncertainty. In data from 126 international alliances, the positive relationship between trust and performance is stronger under high behavioral uncertainty and weaker under high environmental uncertainty. We conclude that partners should concentrate on developing interorganizational trust where potential improvement in alliance performance justifies this effort, which in turn depends on the type of uncertainty faced.